Banana cream pie murder [compact disc, unabridged] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2017)
Upon returning from her honeymoon, Hannah learns that her mother's neighbor has been murdered, but she rejects the police's finding that it was the work of a random intruder and sifts through a growing number of suspects in search of the truth.